Evaluation of Phenotypic and Genetic Characteristics of Dryobalanops aromatica (Dipterocarpaceae) Seedlings Growing in Peat and Mineral Media - Dwiyanti, Fifi Gus; Kustiyarini, Nur Fadila; Kamiya, Koichi; Rachmat, Henti Hendalastuti; Majiidu, Muhammad; Wati, Ridha; Siregar, Iskandar Zulkarnaen (Bogor Agricultural University, Indonesia, 2025)
The selection of tree species suitable for restoration in diverse site conditions is still a challenge. Therefore, this study aimed to analyze the phenotypic and genetic characteristics of Dryobalanops aromatica seedlings growing in mineral soil media and peat media. Phenotypic characteristics were evaluated by analyzing the growth performance, leaf morphological characteristics, leaf color, and chlorophyll content, while genetic characteristics were evaluated by using microsatellite markers. The study revealed that seedlings planted in peat media exhibited greater height and shoot length growth, although the difference was not statistically significant compared to those in mineral soil media. However, seedlings in mineral soil media displayed a significantly higher survival rate than those in peat media. Peat-grown seedlings had higher chlorophyll content in their leaves, while mineral soil-grown seedlings displayed a lighter green leaf color based on digital analysis. Genetic analysis indicated a high genetic diversity of overall D. aromatica seedlings (He = 0.635) and unclear genetic structure between the two media. Overall, these findings demonstrate the successful adaptation of D. aromatica seedlings to peat media, positioning them as a promising choice for peatland restoration.